Integrative analysis of transcriptomics and metabolomics reveals the hepatotoxic mechanism of thiamethoxam on male Coturnix japonica. (15th January 2022) - Pan, Yifan; Chang, Jing; Wan, Bin; Liu, Zijun; Yang, Lu; Xie, Yun; Hao, Weiyu; Li, Jianzhong; Xu, Peng
Abstract: Thiamethoxam (TMX), a representative neonicotinoids, is widely used for seed coating. The consumption of TMX-coated seeds posed threat to birds during crop sowing. The hepatotoxicity of TMX has been reported in mammals, however, no clear evidence showed TMX-induced toxic effects on bird liver. In this study, male Japanese quails ( Coturnix japonica ) were exposed to 20 or 200 mg/kg TMX-treated bird feed for 28 days. Results showed that Clothianidin (CLO), a TMX metabolite preferred to accumulate in quail plasma and liver, and inflammatory cell infiltration was found in quail livers. Oxidative stress-related biological processes were significantly enriched in both TMX treatment groups through transcriptomics analysis. Moreover, integrative analysis of transcriptomics and metabolomics indicated ferroptosis and DNA damage was implicated in hepatotoxicity caused by high- and low-concentration of TMX exposure, respectively. High-dose TMX treatment decreased CAT activity and GSH concentration and increased expression of the ferroptosis-related gene. In addition, the up-regulation of 8-OHdG concentration and DNA repair-related genes expression demonstrated low-dose TMX triggered oxidative DNA damage. The present results highlight the toxicity of TMX to bird livers and contribute to a better understanding of the TMX toxic mechanism in birds. Graphical abstract: Image 1 Highlights: TMX induced hepatotoxicity on quails at environmentally relevant concentration. Bi-omics revealed hepatotoxic mechanism of TMX. TMX impaired oxidative stress function of quail livers. Oxidative damage caused by TMX further triggered DNA damage and ferroptosis.